Benzocaine-loaded polymeric nanocapsules: Study of the anesthetic activities - Silva de Melo, Nathalie Ferreira [UNESP]; De Araujo, Daniele Ribeiro; Grillo, Renato [UNESP]; Moraes, Carolina Morales; De Matos, Angelica Prado; de Paula, Eneida; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Wiley-Blackwell, 2012)
This paper describes a comparison of different polymeric nanocapsules (NCs) prepared with the polymers poly(d,l-lactide-co-glycolide), poly(l-lactide) (PLA), and poly(e-caprolactone) and used as carrier systems for the local anesthetic (LA) benzocaine (BZC). The systems were characterized and their anesthetic activities investigated. The results showed particle size distributions with polydispersity indices below 0.135, average diameters up to 120nm, zeta potentials up to -30mV, and entrapment efficiencies around 70%. Formulations of BZC using the polymeric NCs presented slower release profiles, compared with that of free BZC. Slowest release (release constant, k = 0.0016min(-1)) was obtained using the PLA NC system. Pharmacological evaluation showed that encapsulation of BZC in PLA NCs prolonged its anesthetic action. This new formulation could potentially be used in future applications involving the gradual release of local anesthetics (LAs). (c) 2011 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 101:11571165, 2012
Keywords: benzocaine; polymeric nanocapsule; biodegradable polymers; local anesthetic; in vivo; analgesia; controlled release; poly(lactic; glycolic) acid (PLGA; PLA); nanocapsules; nanotechnology